Pregnancy and ischemic stroke: a practical guide to management. Issue 1 (February 2018) - van Alebeek, Mayte E.; de Heus, Roel; Tuladhar, Anil M.; de Leeuw, Frank-Erik
Abstract : Purpose of review: Ischemic stroke during pregnancy or the puerperium is a devastating disease during a crucial period in life and warrants a specific approach. To date, current practice is mainly based on expert opinion because of a lack of randomized controlled trials and high-quality observational studies. The present review is intended as a practical guide to (acute) management of ischemic stroke during pregnancy and puerperium. Recent findings: Recent findings showed that the incidence of stroke during pregnancy is rising. In 2014, the first guideline for the prevention of stroke in women was released, however on many (pregnancy) related topics the evidence was too scarce to make clear evidence-based recommendations. Summary: The risk of ischemic stroke is elevated especially from the third trimester until 6 weeks postpartum. MRI is the most accurate and well tolerated diagnostic option but low-dose CT-head is a valid alternative. Reperfusion therapies should not be withheld from a pregnant woman with moderate-to-severe stroke when benefits outweigh the risk. Aspirin up to 150 mg daily is considered well tolerated during pregnancy and lactation period. Multidisciplinary care is essential when counseling these women in the acute and later stages.